2020
DOI: 10.47544/johsk.2020.1.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Participation During the COVID-19 Pandemic

Abstract: Physical activity is a significant factor in enhancing quality of life due to its various physical and mental benefits. According to the World Health Organization (WHO, 2010), the recommended amount of physical activity for adults (>17 years old) is a minimum of 150 minutes of moderate-intensity activity or 75 minutes of vigorous-intensity activity every week, while the recommended amount for children and adolescents (5-17 years old) is at least 60 minutes of moderate-to-vigorous physical activity daily. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…and others identifying the 3 main constraints being evaluated. From these data, the researchers identified 3 time periods of athlete development, which they named the "Developmental Model of Sports Participation": (1) sampling years (ages 6-13), (2) specialization years (ages [13][14][15], and (3) investment years (ages 15+ years). 5 Sampling years take place between the ages of 6 and 13 years with emphasis on multisport participation (sampling) and parent responsibility for exposing their children to sports.…”
Section: Developmental Model Of Sports Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…and others identifying the 3 main constraints being evaluated. From these data, the researchers identified 3 time periods of athlete development, which they named the "Developmental Model of Sports Participation": (1) sampling years (ages 6-13), (2) specialization years (ages [13][14][15], and (3) investment years (ages 15+ years). 5 Sampling years take place between the ages of 6 and 13 years with emphasis on multisport participation (sampling) and parent responsibility for exposing their children to sports.…”
Section: Developmental Model Of Sports Participationmentioning
confidence: 99%
“…This shift has led more youth to specialize in a single sport at an earlier age. 13,15,16 Recent studies, however, have shown that early sports specialization may be a risk factor for overuse injury and burnout. 22 Several models for youth athlete development (YAD) provide guidance for specialized athletes aiming to achieve elite performance while minimizing risk for injury.…”
mentioning
confidence: 99%